PENGARUH MEDIA PEMBELAJARAN GEO-FOLD MAGNET TERHADAP PRESTASI BELAJAR DAN VISUALISASI SPASIAL SISWA - Sakira Kusuma Ayu Maharani; Kharisma Juwita Putri; Dessy Ratnasari; Made Diyah Putri Martinasari (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the effect of using the geo-fold magnet learning media on improving students’ learning achievement and spatial visualization skills in geometry. The research employed a mixed-methods approach, combining quantitative and qualitative methods. The subjects consisted of 138 students and six mathematics teachers from SMP Negeri 5, SMP Negeri 6, and SMP Negeri 7 Kota Blitar. The quantitative approach involved pre-test and post-test, while the qualitative approach included questionnaires and interviews. Quantitative data were analyzed using descriptive statistics and a paired sample t-test, whereas qualitative data were processed through data reduction, presentation, and conclusion drawing. The results revealed a significant improvement between the pre-test mean score (61.2) and post-test mean score (84.6), with a significant value less than 0.05, indicating a significant difference after implementing the geo-fold magnet media. Additionally, 92% of students reported that the media helped them better understand geometric shapes and spatial relationships and teachers rated the media with an average score of 3.71. Therefore, the geo-fold magnet media proved effective in enhancing students’ learning achievement and spatial visualization abilities in geometry learning.